2000
DOI: 10.1105/tpc.12.6.933
|View full text |Cite
|
Sign up to set email alerts
|

Syncytial-Type Cell Plates: A Novel Kind of Cell Plate Involved in Endosperm Cellularization of Arabidopsis

Abstract: Cell wall formation in the syncytial endosperm of Arabidopsis was studied by using high-pressure-frozen/freeze-substituted developing seeds and immunocytochemical techniques. The endosperm cellularization process begins at the late globular embryo stage with the synchronous organization of small clusters of oppositely oriented microtubules ( ‫ف‬ 10 microtubules in each set) into phragmoplast-like structures termed mini-phragmoplasts between both sister and nonsister nuclei. These mini-phragmoplasts produce a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(69 citation statements)
references
References 47 publications
6
63
0
Order By: Relevance
“…In addition, we document the presence of molecules that link vesicles and membranous tubules during cell plate formation and the delivery of the ribosome-excluding cell plate assembly matrix to the division plane together with the vesicles. This report, together with recent studies on high-pressure-frozen/ freeze-substituted endosperm samples (Otegui and Staehelin 2000b;Otegui et al 2001), demonstrates that in different tissues of higher-plant cells cytokinesis can proceed by formation of different types of cell plate but never involves cleavage furrows.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…In addition, we document the presence of molecules that link vesicles and membranous tubules during cell plate formation and the delivery of the ribosome-excluding cell plate assembly matrix to the division plane together with the vesicles. This report, together with recent studies on high-pressure-frozen/ freeze-substituted endosperm samples (Otegui and Staehelin 2000b;Otegui et al 2001), demonstrates that in different tissues of higher-plant cells cytokinesis can proceed by formation of different types of cell plate but never involves cleavage furrows.…”
Section: Introductionsupporting
confidence: 54%
“…A cell plate assembly matrix that excludes ribosomes is delivered to the division plane together with the first vesicles Previously, we have shown that a dense, ribosomeexcluding matrix surrounds the early membrane intermediates of developing syncytial-type cell plates (Otegui and Staehelin 2000b;Otegui et al 2001). We have also detected a similar matrix encompassing all the assembly intermediates during post-meiotic cell plates (Figs.…”
Section: Filamentous Structures Link Vesicles and Membranous Tubules mentioning
confidence: 59%
See 2 more Smart Citations
“…In most monocots XG contains less xylose and galactose and does not contain terminal fucose. The structure and molecular distribution of the side chains varies in different plant tissues and species (100)(101)(102).…”
Section: Xyloglucanmentioning
confidence: 99%